Capricious, or tied to history's apron strings? Floristic regions in north‐west European brambles (Rubus subgenus Rubus, Rosaceae). (29th February 2016) - Haveman, Rense; Bijlsma, Rienk‐Jan; de Ronde, Iris; Schaminée, Joop H. J.
Abstract: Aim: To classify and describe distributional patterns in apomictic Rubus subgenus Rubus in north‐west Europe and to characterize the major regions by statistically derived character species. Location: North‐western Europe, in particular Ireland, the United Kingdom, the Netherlands, Denmark and Germany. Methods: We usedtwinspan analysis to distinguish hierarchically ordered phytogeographical regions using grid‐based distributional patterns of bramble species, Dufrêne–Legendre indicator species analysis to define character species for the regions, and descriptive statistical analysis of broad‐scale abiotic factors derived from the LANMAP landscape classification for each region. Results: Grid cells were classified into 114 initial groups and 12 regions (florulas), forming three major bramble territories. Up to 15 indicator species could be assigned to each florula. The florulas in the British Isles are geographically isolated, unlike those on the continent. The florulas differ in minimum temperature in January, mean precipitation in August, and elevation. Although a clear view of the relationship between the bramble flora in the British Isles and the continental flora is obscured by the lack of data from Belgium and France, the major biogeographical patterns coincide with the genetic structure of the genus as published by Sochor et al . (2015 ). Other factors forming the basis for the observed patterns are isolation (especially in the British Isles), and arguably also landscape history and landscape patterns. Main conclusions: Phytogeographical patterns in Rubus subg. Rubus are strongly influenced by historical factors and can be traced back to the hybridization of sexual Rubus ulmifolius, Rubus canescens and Rubus ser. Glandulosi especially. Geographical and ecological factors also play a role in the realization of large‐scale patterns, but these factors seem to be closely tied to the history and genetic structure of the genus through inherited ecology from the ancestral species.